Istanbul Local Government Policy on Managing Syrian Refugees Integration - Audi Izzat Muttaqien; Sidik Jatmika (Journal of Islamic World and Politics, 2023)
The integration of Turkish refugees is a policy of harmonizing refugees into society, and the Istanbul local government tries to implement policies in the same direction as the Turkish Central Government. This article examines the policies and role of the Istanbul government in handling Syrian refugees in the Istanbul area in refugee integration. Turkey has been one of the largest recipients and donors of aid for Syrian refugees. Meanwhile, Istanbul has been a place where many migrants live, especially Syrian refugees. This research uses qualitative methods by collecting data through literature studies and descriptive data analysis. The article uses the cosmopolitanism theory to explain how the Istanbul government's policy in accepting refugee arrivals and its intention to help refugees are based on humanitarian principles. The findings showed that the lack of clarity in the Turkish government's general policy, which does not provide general standards and procedures for refugee integration, caused the Istanbul local government to adopt adaptive policies. Health and education are still the main challenges constrained by resources and funds. The assistance the Istanbul government provides Syrian refugees is motivated by humanitarian reasons, where the Istanbul government views Syrian refugees as human beings with the same rights as other Turkish citizens through a cosmopolitanism approach.